'I'm going to feel stressed, but now I know how to handle it': reducing test anxiety and improving student well‐being at GCSE. Issue 2 (13th July 2022) - Brown, Kerry; Woods, Kevin; Nuttall, Clare
Abstract : Test anxiety has become a widespread issue in many contemporary societies, having a significant detrimental effect on the attainment, health and well‐being of many young people. This paper evaluates a school‐based, multimodal test anxiety intervention framework, 'Every Little Helps' (ELH), developed by educational psychologists and delivered to small groups of GCSE students (aged 15–16) in two secondary schools in the North West of England. A quasi‐experimental, mixed methods approach was adopted. Findings suggest that ELH is helpful in reducing test anxiety amongst GCSE students. Participants report a range of helpful outcomes including an increased sense of control and competence through increased academic attainment, enhanced control of emotions and more helpful ways of thinking. Participants also report beneficial wider impacts as a result of being able to generalise learnt skills and techniques to other aspects of their lives. Implications for educational policy and practice and future research are considered.